PENGARUH APLIKASI SIK-ASIEK TERHADAP PENGETAHUAN DAN SIKAP TENTANG ASI EKSKLUSIF - Juhanida Lestari, Pratiwi; Agushybana, Farid; Achadi Nugraheni, Sri (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background: The spread of health information about breastfeeding can take advantage of smartphone technology. Utilization of the application of the Exclusive ASI Health Information System (Sik-Asiek) as a source of information about exclusive breastfeeding and breastfeeding support from peers and health workers through chat group features found in the Sik-Asiek application. Objective: Analyze the effect of the application of Sik-Asiek applications on knowledge and attitudes of exclusive breastfeeding. Methods: The study used a quasi experimental non equivalent control group design with pretest and posttest. The research respondents were third trimester pregnant women, amounting to 72 people. Knowledge and attitudes of mothers before and after the application of Sik-Asiek applications were measured using a questionnaire while the practices were measured using observation sheets after treatment. Data analysis using independent test sample t-test, Mann-Whitney test and Manova. Results: there is the effect of applying the Sik-Asiek application on mothers to knowledge (p-value 0,00), and attitudes (p-value 0,00) for exclusive breastfeeding practices. Conclusion: The application of